Engaging rural communities in Bangladesh to tackle antimicrobial resistance through the Community Dialogue Approach: a process evaluation protocol for COSTAR project in Cumilla, Bangladesh - Saify, Md Badruddin; Jones, Nichola; Fieroze, Fariza; Mitchell, Jessica; Hicks, Joseph Paul; Huque, Samina; Saha, Sajib; Latham, Sophia; Hawkings, Helen; Huque, Rumana; King, Rebecca (Frontiers in Public Health, 2024)
IntroductionAntimicrobial resistance (AMR) is a global problem and is especially threatening for low-and-middle income countries like Bangladesh. The COSTAR (Community-led Solutions to Antimicrobial Resistance) project includes a Randomised Control Trial (RCT) which aims to evaluate the effectiveness of the Community Dialog Approach (CDA) to improve levels of correct and appropriate knowledge and reported practice about antibiotics, antibiotic use, and antibiotic resistance (ABR) from a One Health perspective, among adult community members in 5 selected sub-districts of Cumilla. The CDA is a community engagement approach involving community members in active discussions also known as Community Dialogs (CD), run by local facilitators. The dialogs promote collective action to produce sustainable social change. The trial’s process evaluation will evaluate fidelity, dose, adaptation, reach, mechanisms of impact and the process of knowledge diffusion using the MRC framework for the evaluation of complex interventions.Methods and analysisThe process evaluation will be implemented in the catchment areas of 25 selected community clinics (CCs) in the intervention group. The key actors involved in the process evaluation are participants from master trainers and trainers training; community dialog facilitators; supervisors; community dialog participants and non-participants; and local and national level government stakeholders. Qualitative and quantitative data will be collected through Focus Group Discussion (FGDs); Case Studies; Key Informant Interview (KIIs); CD observations; monitoring forms; quarterly feedback from facilitators and supervisors, and pre-and-post-test questionnaires administered during the training of facilitators. All qualitative data will be coded using a priori coding framework in NVIVO 14. Quantitative data will be analysed using descriptive statistics.Ethics and disseminationEthical approval was obtained from the Bangladesh Medical Research Council (BMRC): BMRC/NREC/2019–2022/427 and from the University of Leeds Faculty of Medicine and Health ethics board: MREC 20–034. All results will be disseminated through a one pager summary; infographics; peer-reviewed journal articles and national and international conferences.Clinical trial registrationhttps://www.isrctn.com/ISRCTN93756764, identifier ISRCTN93756764.